Extracting carbon emission for industrial area by using Landsat 8: case study of Klang, Malaysia - ruqayyah, Mohd Zaini; Hj. Mohd. Noor, Norzailawati; Mazlan, Hashim (2020)
Industrial area attributed to 235.6% carbon emissions increase from 1990 to 2005. In 2009 Malaysia announced a voluntary commitment to reduce 40% of its greenhouse gases (GHG) emissions by 2020. The study aims to extract the carbon emission by industrial area using Landsat 8 processed through Land Surface Temperature (LST) data in quantifying carbon. The data required are obtained from the Sniffer4D drone, Landsat 8 LST and Department of Environment (DOE) data, which were analysed through comparative and statistical analysis. The findings showed that the high correlation of Site A, (= 0.7403) Site B, (= 0.607) and Site C, (= 0.0026) strength between data from the drone and satellite data. As a results, that band11 Thermal Infrared (TIRS) 2 in Landsat 8 can be used for extracting carbon value estimation and band 10 Thermal Infrared (TIRS) 1 for the measurement of the air temperature. These findings can assist in terms of calculating carbon emission using LST and determine the high concentration industrial carbon emission hence it can help in decision making in further industry area development